Willingness of farmers to use treated wastewater for irrigation in the West Bank, Palestine. Issue 3 (4th May 2022) - Hamdan, Maher; Abu-Awwad, Ahmad; Abu-Madi, Maher
ABSTRACT: Limited water resources are among the main obstacles to development in Palestine. This research investigates farmers' perceptions and willingness to use treated wastewater (TWW) for irrigation. Despite the availability of large quantities of TWW, just 11% of the interviewed farmers use it in irrigation. Just 24% of them confirmed that they had participated in awareness workshops related to TWW, but 75% stated they would be willing to use TWW for irrigation. We find that the main obstacles to the use of TWW in irrigation are availability of freshwater, non-availability of TWW and psychological aversion.